Productive configuration and territorial development. Comparative study between north and south of the Aburrá Valley (Revista "Boletín el Conuco", 2022)
The development of the territories depends on a wide range of dimensions that go beyond the economic. However, each territory has its peculiarities and this also leads to different levels of development. Thus, this article aims to analyze the territorial aspects that explain the differentiation of development between the South and the North of the Aburra Valley. A qualitative methodology was used with the use of quantitative tools such as descriptive statistics, cartography and literature review. It is concluded that the current higher levels of development in the South of the Aburra Valley compared to the North are due to a better productive organization, greater articulation between local actors and their business reality.
Keywords: productive organization; regional analysis; regional development